Modulation by monovalent anions of calcium and caffeine induced calcium release from heavy sarcoplasmic reticulum vesicles - Hasselbach, Wilhelm; Migala, Andrea (Zeitschrift für Naturforschung. C, a journal of biosciences, 1992)
Both calcium and caffeine induced calcium release from actively loaded heavy sarcoplasmic reticulum vesicles were studied to analyze the dependence of both activities on the composition of the release medium with respect to monovalent anions. Calcium is unable to induce net calcium release while caffeine remains effective as releasing agent when the experimental media contain neither chloride nor nitrate ions. Caffeine induced calcium release is not suppressed by chelating residual medium calcium (approximately 0 .5 -1 μᴍ) with 2 mᴍ EGTA added 15 s prior to 10 mᴍ caffeine. Calcium release from vesicles loaded in media containing 0.2 ᴍ gluconate as monovalent anion is induced when the medium is supplemented with chloride or nitrate. The release amplitude increases linearly when K-gluconate is replaced by KCl. At constant ionic strength the release amplitude becomes maximal at a chloride concentration of 0.2 ᴍ. The chloride effect completely disappears when 2 mᴍ EGTA are added simultaneously. When chloride is replaced by nitrate, as releasing agent, maximal release is achieved already by addition of 0.1 ᴍ K-nitrate. The releasing effect of nitrate can only partially be suppressed by EGTA. The different effectiveness of gluconate, chloride and nitrate as calcium release supporting ions corresponds to their activating effect on the binding of ryanodine to the calcium release channel in the vesicular membranes.